THU0182 PHARMACOKINETICS AND SAFETY OF A SINGLE ORAL DOSE OF PEFICITINIB (ASP015K) IN SUBJECTS WITH NORMAL AND IMPAIRED RENAL FUNCTION. (June 2019) - Miyatake, Daisuke; Shibata, Tomohisa; Shibata, Mai; Kaneko, Yuichiro; Oda, Kazuo; Nishimura, Tetsuya; Katashima, Masataka; Sekino, Hisakuni; Furihata, Kenichi; Urae, Akinori
Abstract : Background: Peficitinib (ASP015K), a novel oral Janus kinase inhibitor, was shown to be efficacious as once-daily therapy for moderate-to-severe rheumatoid arthritis (RA) in a phase 2b study (NCT01649999 ) 1 and in two phase 3 studies (NCT02308163 2 and NCT02305849 ). 3 Mean urinary excretion of peficitinib accounted for 9–15% of the oral dose. 4 Objectives: To assess the pharmacokinetics (PK) and safety of a single, oral dose of peficitinib 150 mg in subjects with normal and impaired renal function. Methods: This was an open-label, single-dose, parallel-group study conducted at two centres in Japan. All subjects were aged 20–75 years with a body mass index ≥17.6 to <30.0 kg/m 2 . Renal function was classified according to estimated glomerular filtration rate (eGFR) using a GFR predictive equation for Japanese subjects: normal ≥90 mL/min/1.73 m 2 ; mild impairment ≥60 to <90 mL/min/1.73 m 2 ; moderate impairment ≥30 to <60 mL/min/1.73 m 2 ; and severe impairment ≥15 to <30 mL/min/1.73 m 2 . Subjects with impaired renal function had unchanged renal impairment treatment (including diet) within 14 days prior to dosing. Subjects received a single, oral dose of peficitinib 150 mg tablet under fasting conditions in a hospital setting. The selected dose was based on the peficitinib daily dose in the phase 3 RA studies. Blood samples for peficitinib plasma PK analysis were collected before administration and up to 72 h post dose. Safety was assessed throughout the study. Results: A total of 31 subjects (87.1% male; Table 1 ) were enrolled and received study drug according to study protocol. Subjects comprised 8 with normal renal function, and 8 with mild, 8 with moderate and 7 with severe renal impairment. The peficitinib concentration–time profiles from dosing to 72 h (Fig. 1 ), extrapolated to infinity (AUCinf ) and maximum concentration (Cmax ) were similar between those with normal and impaired renal function (Table 2 ). Two subjects had mild/grade 1 (CTCAE v4.0 JCOG) treatment-emergent adverse events (TEAEs): 1/8 (12.5%) with normal renal function had a headache (considered to be drug-related) and 1/8 (12.5%) with mild renal impairment had increased alanine aminotransferase (ALT) (not considered to be drug-related). There were no serious TEAEs or deaths during the study. There were no clinically significant mean changes from baseline in other clinical laboratory parameters or vital sign measurements, except for grade 1 increased ALT in a subject with mild renal impairment. Conclusion: Exposure after a single 150 mg oral dose of peficitinib under fasting conditions was similar between subjects with and without renal impairment. The peficitinib dose was generally well tolerated, with no differences in TEAE incidence by renal function. References: [1]Takeuchi T, et al. Ann Rheum Dis 2016; 75: 1057–64; 2. Tanaka Y, et al. ACR/ARHP Annual Meeting 2018: Abstract 887; 3. Takeuchi T, et al. ACR/ARHP Annual Meeting 2018: Abstract 888; 4. Cao YJ, et al. Clin Pharmacol Drug Dev 2016;5:435–49 Acknowledgement: This study was sponsored by Astellas Pharma, Inc. Medical writing support was provided by Rhian Harper Owen of Cello Health MedErgy and funded by Astellas Pharma, Inc. Disclosure of Interests: Daisuke Miyatake Employee of: Astellas Pharma, Inc., Tomohisa Shibata Employee of: Astellas Pharma, Inc., Mai Shibata Employee of: Astellas Pharma, Inc., Yuichiro Kaneko Employee of: Astellas Pharma, Inc., Kazuo Oda Employee of: Astellas Pharma, Inc., Tetsuya Nishimura Employee of: Astellas Pharma, Inc., Masataka Katashima Employee of: Astellas Pharma, Inc., Hisakuni Sekino Grant/research support from: Astellas Pharma, Inc., Kenichi Furihata Grant/research support from: Astellas Pharma, Inc., Akinori Urae Grant/research support from: Astellas Pharma, Inc.